Intravenous iron and chronic obstructive pulmonary disease: a randomised controlled trial - Nayia Petousi; Nick P Talbot; Peter A Robbins; Mona Bafadhel; Annabel H Nickol; Peter Santer; Matthew C Frise; Anne McGahey; Richard Baskerville (BMJ Open Respiratory Research)
Background Increased iron availability modifies cardiorespiratory function in healthy volunteers and improves exercise capacity and quality of life in patients with heart failure or pulmonary hypertension. We hypothesised that intravenous iron would produce improvements in oxygenation, exercise capacity and quality of life in patients with chronic obstructive pulmonary disease (COPD).Methods We performed a randomised, placebo-controlled, double-blind trial in 48 participants with COPD (mean±SD: age 69±8 years, haemoglobin 144.8±13.2 g/L, ferritin 97.1±70.0 µg/L, transferrin saturation 31.3%±15.2%; GOLD grades II–IV), each of whom received a single dose of intravenous ferric carboxymaltose (FCM; 15 mg/kg bodyweight) or saline placebo. The primary endpoint was peripheral oxygen saturation (SpO2) at rest after 1 week. The secondary endpoints included daily SpO2, overnight SpO2, exercise SpO2, 6 min walk distance, symptom and quality of life scores, serum iron indices, spirometry, echocardiographic measures, and exacerbation frequency.Results SpO2 was unchanged 1 week after FCM administration (difference between groups 0.8%, 95% CI −0.2% to 1.7%). However, in secondary analyses, exercise capacity increased significantly after FCM administration, compared with placebo, with a mean difference in 6 min walk distance of 12.6 m (95% CI 1.6 to 23.5 m). Improvements of ≥40 m were observed in 29.2% of iron-treated and 0% of placebo-treated participants after 1 week (p=0.009). Modified MRC Dyspnoea Scale score was also significantly lower after FCM, and fewer participants reported scores ≥2 in the FCM group, compared with placebo (33.3% vs 66.7%, p=0.02). No significant differences were observed in other secondary endpoints. Adverse event rates were similar between groups, except for hypophosphataemia, which occurred more frequently after FCM (91.7% vs 8.3%, p<0.001).Conclusions FCM did not improve oxygenation over 8 weeks in patients with COPD. However, this treatment was well tolerated and produced improvements in exercise capacity and functional limitation caused by breathlessness. These effects on secondary endpoints require confirmation in future studies.Trial registration number ISRCTN09143837.